2015
DOI: 10.5539/gjhs.v8n5p231
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Sleep Quality and Social Intimacy, and Academic Burn-Out in Students of Medical Sciences

Abstract: Introduction:Academic burnout leads to creation of a series of negative and scattered thoughts, loss of hope and emotional and physical exhaustion in carrying out activities. Two factors that affect academic burnout are sleep quality and social intimacy. This study was conducted in order to investigate the relationship between sleep quality and social intimacy, and academic burn-out in the students of Tabriz University of Medical SciencesMaterials & Methods:This study was descriptive and correlational. The pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 14 publications
(21 reference statements)
0
23
2
4
Order By: Relevance
“…[ 14 ] Prior studies have demonstrated that sleeping impairment decreased concentration and increased burnout. [ 15 , 16 ] However, in contrast to previous research, our study did not find an association between sleep time with burnout. [ 17 ] Considering the fact that our data regarding sleep time and sleep quality were all self-reported, the definite relationship between sleep and burnout in residents in SRT should be explored in future study through sleep monitoring.…”
Section: Discussioncontrasting
confidence: 99%
“…[ 14 ] Prior studies have demonstrated that sleeping impairment decreased concentration and increased burnout. [ 15 , 16 ] However, in contrast to previous research, our study did not find an association between sleep time with burnout. [ 17 ] Considering the fact that our data regarding sleep time and sleep quality were all self-reported, the definite relationship between sleep and burnout in residents in SRT should be explored in future study through sleep monitoring.…”
Section: Discussioncontrasting
confidence: 99%
“…Ultimately, lack of efficacy related to school emerges as states like low sense of competency, low progress and lack of sense of success in school assignments and on the whole, in school. (47). Explaining this similarity, we can say that EI is a set of acquired abilities, capabilities and skills and inherited talent, so the promotion of EI requires special educational measures and age alone cannot increase or decrease it.…”
Section: Discussionmentioning
confidence: 99%
“…Specific grading schemes have been independently associated with burnout; students were found to be more likely burned out and with high stress in schools with letter grading as opposed to pass/fail[13]. Other studies have found associations with perfectionism, low academic self-efficacy[14], more advanced year of training, negative personal life events in the last 12 mo[15], alcohol abuse and dependence[16], and decreased social intimacy[17]. Sleep quality[17], pathological sleepiness, and sleeping less than seven hours a night also seem to independently predict burnout, however exercise does not[18].…”
Section: Introductionmentioning
confidence: 99%